2022
DOI: 10.3390/polym14091677
|View full text |Cite
|
Sign up to set email alerts
|

Biocompatible Nanoparticles Based on Amphiphilic Random Polypeptides and Glycopolymers as Drug Delivery Systems

Abstract: In this research, the development and investigation of novel nanoobjects based on biodegradable random polypeptides and synthetic non-degradable glycopolymer poly(2-deoxy-2-methacrylamido-D-glucose) were proposed as drug delivery systems. Two different approaches have been applied for preparation of such nanomaterials. The first one includes the synthesis of block-random copolymers consisting of polypeptide and glycopolymer and capable of self-assembly into polymer particles. The synthesis of copolymers was pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 70 publications
4
17
0
Order By: Relevance
“…The higher IC 50 values determined for PTX nanoformulations can be explained by the gradual accumulation of PTX in the medium due to the drug release as opposed to free PTX, whose concentration in the medium is initially defined and constant. The results obtained in this study are similar to those of the previously reported PTX delivery systems based on glycopolymers [ 31 ] or PEGylated phospholipid microparticles [ 67 ].…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…The higher IC 50 values determined for PTX nanoformulations can be explained by the gradual accumulation of PTX in the medium due to the drug release as opposed to free PTX, whose concentration in the medium is initially defined and constant. The results obtained in this study are similar to those of the previously reported PTX delivery systems based on glycopolymers [ 31 ] or PEGylated phospholipid microparticles [ 67 ].…”
Section: Resultssupporting
confidence: 90%
“…Due to their biocompatibility and biodegradability to non-toxic metabolites, the amphiphilic polypeptides are very promising candidates for the delivery of various drug [ 29 , 30 , 31 , 32 , 33 ]. There are a number of works devoted to the development of the polypeptide-based conjugates and nanoparticles as delivery systems for peptides [ 34 , 35 ], nucleic acids [ 36 , 37 ], cytostatic drugs [ 38 , 39 , 40 ] and some others [ 41 ].…”
Section: Introductionmentioning
confidence: 99%
“…Here, PMX B was conjugated with P(Glu-co-Phe) and PGlu to compare the properties of physically loaded and covalently bound PMX B. In addition, two synthetic biocompatible polymers, namely poly(2-deoxy-2-methacrylamido-D-glucose) (PMAG) [30] and copolymer of vinyl succinamic acid and N-vinylsuccinimide (P(VSAA-co-VSI)) [31], were also investigated as carriers for PMX B conjugation. The composition of PMX B polymer conjugates was optimized in terms of conjugation efficacy and physicochemical characteristics of conjugates.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, using sugar moieties as ligands of either GLUTs or CD44 to actively target cancer cells is becoming one of the important strategies in cancer therapy. Glycopolymers are synthetic macromolecules having pendant sugar moieties and widely used to target cancer cells. , They are usually utilized as the hydrophilic segment of amphiphilic block copolymers to fabricate micelles as drug carriers. , One of these glycopolymers is poly­(2-deoxy-2-methacrylamido- d -glucose) (PMAG) mostly obtained by reversible addition fragmentation chain transfer (RAFT) polymerization and has been extensively studied in delivery applications. Since PMAG is hydrophilic, it is usually combined with hydrophobic segments including poly­( l -lysine- co - L -phenylalanine), poly­[( N -(2-aminoethyl) methacrylamide], poly­[ N -[3-( N,N -dimethylamino) propyl] methacrylamide], and poly­( O -cholesteryl methacrylate) to fabricate core–shell micelles. Such polymeric micelles are useful in both passive targeting due to their sizes (enhanced permeation and retention effect) and active targeting via glucose groups leading to decreased systemic toxicity and side effects.…”
Section: Introductionmentioning
confidence: 99%
“… 51 , 52 One of these glycopolymers is poly(2-deoxy-2-methacrylamido- d -glucose) (PMAG) mostly obtained by reversible addition fragmentation chain transfer (RAFT) polymerization and has been extensively studied in delivery applications. Since PMAG is hydrophilic, it is usually combined with hydrophobic segments including poly( l -lysine- co - L -phenylalanine), 53 poly[( N -(2-aminoethyl) methacrylamide], 54 poly[ N -[3-( N,N -dimethylamino) propyl] methacrylamide], 55 and poly( O -cholesteryl methacrylate) 56 to fabricate core–shell micelles. Such polymeric micelles are useful in both passive targeting due to their sizes (enhanced permeation and retention effect) 57 and active targeting via glucose groups 40 leading to decreased systemic toxicity and side effects.…”
Section: Introductionmentioning
confidence: 99%